Ultrasound Promoted Simple and Efficient N-Alkylation of 2-Substituted Benzimidazoles - Kishore Babu, P.N.; Rama Devi, B.; Dubey, P.K. (Asian Journal of Chemistry, 2012)
N-Alkylation of 2-chlorobenzimidazole was carried out using different alkylating agents under ultrasound irradiation technique. These reactions were completed in shorter times and with higher percentage of yields. Among all the green solvents, triethanolamine was found to be very effective and also acts as a base. The above reaction conditions were extended to other 2-substituted benzimidazoles. Thus, a simple and efficient route for N-alkylation has been developed using ultrasound irradiation technique.